A Survey of Various Cloud Simulators - Kaur, Harleen; Gautam, Vinay (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is a model for enabling convenient and on-demand network access to a shared pool of configurable computing resources like networks, servers, storage, application and services that can be rapidly provisioned and released with minimal management effort or service provider interaction. These resources are pooled for the usage of customers to cater the elastic need of resources of customers due to varying workload. Clients need to pay only for the amount of resources they use. The need of the hour is to reduce the cost of cloud and increase its efficiency. As the cost of cloud resources is very high, so the solution is to use Simulation tools for designing a cloud service and form experiments with the same. This paper compares various simulating tools namely CloudSim, Green Cloud, MDCSim and Cloud Analyst based on their features, advantages and disadvantages.